2016
DOI: 10.1590/1809-98232016019.140233
|View full text |Cite
|
Sign up to set email alerts
|

Análise de métodos para detectar sarcopenia em idosas independentes da comunidade

Abstract: Introduction: Aging imposes changes in the body composition of individuals. One of the most striking changes during this period is the progressive loss of mass, strength and muscle function, known as sarcopenia. Objectives: To evaluate the presence of sarcopenia in healthy elderly women living in the community through a combination of different methods to assess muscle mass (MM) and physical performance, as well as analyzing whether there is correlation between the different methods of defining sarcopenia. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 37 publications
1
7
1
9
Order By: Relevance
“…However, the World Health Organization (WHO) considers that CC measurement is sensitive for assessment of muscle mass in the elderly, indicating changes that occur during aging and with reduced physical activity. 6 In view of the findings of this study, it is suggested that other methods for evaluation of muscle mass be used with this population, such as imaging exams (for example, magnetic resonance or computed tomography). Techniques for assessing the quantity and quality of muscles are primarily available in research centers, rather than clinical environments.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…However, the World Health Organization (WHO) considers that CC measurement is sensitive for assessment of muscle mass in the elderly, indicating changes that occur during aging and with reduced physical activity. 6 In view of the findings of this study, it is suggested that other methods for evaluation of muscle mass be used with this population, such as imaging exams (for example, magnetic resonance or computed tomography). Techniques for assessing the quantity and quality of muscles are primarily available in research centers, rather than clinical environments.…”
Section: Discussionmentioning
confidence: 96%
“…The test was performed three times and values of ≤ 0.8 m/s were defined as indicative of slow GS. 6,16 Calf circumference was measured using an inelastic tape measure around the largest curvature of the calf with the participant seated on a chair with knees and hips at 90°. Measurements lower than 31 cm were defined as indicative of muscle mass depletion.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…No estudo de Paula et al [20], também foi avaliada a sarcopenia com diferentes combinações de métodos avaliativos, mas a circunferência da panturrilha não mostrou alteração menor que 31 cm, corroborando o presente estudo já que os grupos G1, G2 e G3 apresentaram CP maiores que 31 cm. [21], a velocidade de marcha diminui com o avanço da idade e pode haver uma relação entre a força de membros inferiores e a velocidade de marcha.…”
Section: Discussionunclassified
“…However, there is still broad disagreement regarding the cutoff points that should be adopted [3,4,6,9]. Furthermore, the different methods available to measure ALM and population-speci c differences hamper the understanding and establishment of universal criteria for the screening of sarcopenia [13][14][15].…”
Section: Introductionmentioning
confidence: 99%